The Psychology of Shame: A Resilience Seminar for Medical Students - William E. Bynum; Sebastian Uijtdehaage; Anthony R. Artino; James W. Fox (Association of American Medical Colleges, 2020)
Introduction Shame is a powerful emotion that can cause emotional distress, impaired empathy, social isolation, and unprofessional behavior in medical learners. However, interventions to help learners constructively engage with shame are rare. This module educated medical students about shame, guided them through an exploration of their shame experiences, and facilitated development of shame resilience. Methods In this 2-hour workshop, clinical-year medical students were guided through the psychology of shame through didactic slides. Next, a small panel of volunteer students, recruited and coached prior to the workshop, shared reflections on the content, including their shame experiences during medical school. This was followed by didactic slides outlining strategies to promote shame resilience. Participants then broke into faculty-led small groups to discuss session content. The module included a small-group facilitator guide for leading discussions on shame, didactic slides, discussion prompts, an evaluation tool, and a film entitled The Shame Conversation that was created after the initial workshop. Results A retrospective pre/postsurvey revealed statistically significant increases in: (1) importance ascribed to identifying shame in one's self or colleagues, (2) confidence in one's ability to recover from a shame reaction, and (3) comfort in reaching out to others when shame occurs. Analysis of open-ended questions showed that students felt the seminar would enhance future resilience by helping them identify and normalize shame, distinguish shame from guilt, and reach out to others for help. Discussion This workshop appears to prepare students to more constructively engage with shame when it occurs in medical training.